2009
DOI: 10.1080/13576500802434965
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the stabilising and mobilising features of footedness

Abstract: This study investigated lower limb laterality for stabilising and mobilising actions in 10 right- and 10 mixed-footed participants by determining, via the Waterloo Footedness Questionnaire--Revised (WFQ-R), the preferred foot in carrying out a range of stabilising and mobilising activities and by recording foot performance on standing balance and ball juggling. The log odds ratio (lambda score) was used to quantify the degree of laterality in task performance. Differences between the stability and mobility sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
34

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 53 publications
0
31
0
34
Order By: Relevance
“…The non-paretic side was defined as the predominantly-used hemibody by convenience while the predominantly-used hemibody by preference was assessed by the Waterloo Footedness Questionnaire-Revised (WFQ-R) [5]. The impairments in the affected hemibody were assessed by the Orpington Prognostic Scale (OPS) [12] ranging from 1.6 to 6.8 which classifies the paretic side in light (1.6 6 OPS 6 3.1), moderate (3.1 < OPS 6 5.1) or (OPS > 5.1) severe impaired.…”
Section: Preliminary Data For Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-paretic side was defined as the predominantly-used hemibody by convenience while the predominantly-used hemibody by preference was assessed by the Waterloo Footedness Questionnaire-Revised (WFQ-R) [5]. The impairments in the affected hemibody were assessed by the Orpington Prognostic Scale (OPS) [12] ranging from 1.6 to 6.8 which classifies the paretic side in light (1.6 6 OPS 6 3.1), moderate (3.1 < OPS 6 5.1) or (OPS > 5.1) severe impaired.…”
Section: Preliminary Data For Supportmentioning
confidence: 99%
“…Since the first discoveries about the existence of lateralized functions in the human brain [1], they have been suggested right-left asymmetries to many of the higher cerebral functions, including motor control [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Further research lead to the hypothesis that the nondominant arm controller has become specialized for regulating limb impedance, which is needed to achieve steady-state positions (Bagesteiro & Sainburg, 2003Duff and Sainburg, 2006;Schabowsky et al, 2007). Footedness has been previously reported as an important factor in predicting the motor preparation dependent on the behavioural context of a particular task (Carpes et al, 2007;Gabbard & Iteya, 1996;Grouios et al, 2009). It has been claimed that the footedness may be a better predictor of the cerebral lateralization than the handedness (Elias, Bryden & Bulman-Fleming, 1998;Strauss & Wada, 1983).…”
Section: Laterality and Motor Controlmentioning
confidence: 99%
“…Many researchers [4,5] reported that laterality is found in grip strength of dominant and non-dominant hands with different use frequency in daily life. On the other hand, regarding the lower limb, Grouios et al [6] reported a dominant leg used for maneuvering a ball and the other used for maintaining postural stability. However, Burnie and Brodie [7], Neumann et al [8], and Masuda et al [9] reported that a right-left difference was not found in maximum extension strength of hip and knee joints.…”
Section: Introductionmentioning
confidence: 99%